2017
DOI: 10.1101/225938
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dopaminergic drug treatment remediates exaggerated cingulate prediction error responses in obsessive-compulsive disorder

Abstract: (word count 244)Background: Patients with obsessive-compulsive disorder (OCD) have been found to show

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…This inconsistency may be partially explained by effects of illness duration 36 . In a probabilistic learning paradigm, Murray and colleagues 37 reported that dysfunctions during reward processing in OCD may be of dopaminergic origin, which may be similar to those alterations seen in schizophrenia patients [38][39][40] . Furthermore, in a two-step decision-making task, OCD individuals exhibited more model-free choices in rewarded outcomes and more model-based choices in loss outcomes, with compulsions severity linked to habitual learning of rewarded outcomes and obsessions severity linked to increased choice switching following losses 41 .…”
Section: Introductionmentioning
confidence: 89%
“…This inconsistency may be partially explained by effects of illness duration 36 . In a probabilistic learning paradigm, Murray and colleagues 37 reported that dysfunctions during reward processing in OCD may be of dopaminergic origin, which may be similar to those alterations seen in schizophrenia patients [38][39][40] . Furthermore, in a two-step decision-making task, OCD individuals exhibited more model-free choices in rewarded outcomes and more model-based choices in loss outcomes, with compulsions severity linked to habitual learning of rewarded outcomes and obsessions severity linked to increased choice switching following losses 41 .…”
Section: Introductionmentioning
confidence: 89%